Massive Retinal Pigment Epithelial Detachment Following Acute Hypokalemic Quadriparesis in Dengue Fever - Goel, Neha (J Ophthalmic Vis Res, 2016)
PURPOSE: To describe an unusual retinal manifestation of dengue fever in an endemic region. CASE REPORT: A 35 year old male presenting with acute onset decreased vision in his right eye, was found to have a massive retinal pigment epithelial detachment (PED) extending up to the vascular arcades. He had been diagnosed with acute hypokalemic quadriparesis in dengue fever in the preceding week, which had resolved following treatment. The patient was managed conservatively. At three months follow up, there was spontaneous flattening of the PEDs with improvement in visual acuity. CONCLUSION: Dengue fever complicated by acute hypokalemic quadriparesis can be associated with PED, which can be large. The condition resolves spontaneously and bears a good prognosis.